Macular arteritis associated with concurrent HIV and hepatitis B infections: a case report and evidence for a disease spectrum association with cutaneous polyarteritis nodosa. (6th April 2015) - Kolivras, Athanassios; Thompson, Curtis; Metz, Tanguy; André, Josette
<x xml:space="preserve">Abstract</x> We report the first case of macular arteritis in a 33‐year‐old Black, African female with concurrent human immunodeficiency virus (HIV) and hepatitis B virus (HBV) infections. Of particular interest in macular arteritis is the striking discordance between the clinical presentation and the histopathological findings, a fact that both dermatologists and dermatopathologists should be aware. Histopathologically, the case showed typical findings of macular arteritis with a perivascular, predominantly lymphocytic, infiltrate and intraluminal thrombosis. Both HIV and HBV have been reported as viral inducers of cutaneous polyarteritis nodosa (PAN). Their association with macular arteritis in this case supports existing evidence that macular arteritis and cutaneous PAN represent a single‐disease spectrum of vasculitides, with macular arteritis representing the chronic, lymphocytic and indolent stage, and cutaneous PAN the neutrophilic, acute stage with a risk for systemic progression. Lymphocytic thrombophilic arteritis (LTA), a third, uncommon disease would be in between macular arteritis and cutaneous PAN on a spectrum. Features of this case and other published cases provide strong evidence that there is a single, mild‐to‐severe disease spectrum of macular arteritis‐LTA‐cutaneous PAN.